The benefit of combinations of oximes for the ability of antidotal treatment to counteract sarin-induced brain damage in rats - Filip Caisberger; Jaroslav Pejchal; Jan Misik; Jiri Kassa; Martin Valis; Kamil Kuca (BMC, 2018)
Abstract Background The aim of our study was to compare the ability of two combinations of oximes (HI-6 + trimedoxime and HI-6 + K203) with atropine to counteract acute sarin-induced brain damage with the efficacy of antidotal treatment involving single oxime (HI-6) and atropin using in vivo methods. Methods Brain damage and neuroprotective effects of antidotal treatment were evaluated in rats poisoned with sarin at a sublethal dose (108 μg/kg i.m.; 90% LD50) using histopathological, Fluoro-Jade B and Terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) analysis 24 h after sarin administration. Results Both combinations of oximes reduce the number of rats that died before the end of experiment compared to non-treated sarin poisoning and sarin poisoning treated with HI-6 and atropine. In the case of treatment of sarin poisoning with HI-6 in combination with K203, all rats survived till the end of experiment. HI-6 with atropine was able to reduce sarin-induced brain damage, however, both combinations were slightly more effective. Conclusions The oxime HI-6 in combination with K203 and atropine seems to be the most effective. Thus, both tested oxime combinations bring a small benefit in elimination of acute sarin-induced brain damage compared to single oxime antidotal therapy.